Characterization of hydrodistillated pomelo peel oil and the enhancement of biological activities using microemulsion formulations - Chaiyana,W. (IJPPS, 2015)
© 2014, International Journal of Pharmacy and Pharmaceutical Sciences. All rights reserved. Objective: The present study aims to investigate the compositions and biological activities of essential oil extracted from pomelo peel and develop into microemulsions. Methods: Four subspecies of pomelo including Kao-Namphung (KN), Kao-Puang (KP), Kao-Tang-Gwa (KT), and Kao-Yai (KY) were subjected to the hydrodistillation to yield essential oils. The constituents of each oil was analyzed by GC-MS. Radical scavenging activities were determined by ABTS and DPPH assays, whereas, lipid antioxidant activity was determined by linoleic acid peroxidation assay. Antityrosinase activity and safety on human PBMCs were also investigated. Pseudoternary phase diagrams were constructed to reveal the effects of each compostions on the microemulsion regions. The microemulsion was formulated and chracterized for the particle size, rheological behavior and biological activities. Results: Limonene was the major constituent in KN, KP, KT, and KY oil which was detected up to 86.19%, 85.76%, 79.36%, and 80.20%, respectively. Among four oils, KT oil exhibited the highest radical scavenging, antioxidant and antityrosinase activities. The MTT assay revealed that KT oil had no toxicity on human PBMCs. The microemulsion formulation (ME) containing 15% KT, 36% Tween 20, 9% PEG 400, and 40% water, were formulated and chracterized. ME was transparent liquid with the particle size of 90.28 ± 1.60 nm. ME exhibited the Newtonian flow behavior with low viscosity (16.78 ± 0.12 Pas). In a comparison with KT oil, ME show significant higher radical scavenging and antioxidant activities (p< 0.01). Conclusion: Development of microemulsion increased radical scavenging and antioxidant activities of KT oil and would be an attractive system for further development to effective topical products.